(3GdHjGf aj EYQGH GdbQBfs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj, J (B444 (3g` s ((3QhVI eUQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi NTYJ dg GdCUhGJ hbUQJ Yfg GdUaGJ s
(3BNQgG (B:s
(3agPG eHdZ LgOfG ajeG CaQOfG dg cJGHfG gPG , hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JLhjO hbQGAGJ (B21) s
Keywords: (3GdbQGAGJ hGdJLhjOs